Corrosion Resistance of Sulfur–Selenium Alloy Coatings. Issue 51 (15th October 2021) - Susarla, Sandhya; Chilkoor, Govinda; Kalimuthu, Jawahar R.; Saadi, M. A. S. R.; Cui, Yufei; Arif, Taib; Tsafack, Thierry; Puthirath, Anand B.; Sigdel, Pawan; Jasthi, Bharat; Sudeep, Parambath M.; Hu, Leiqing; et al.
Abstract: Despite decades of research, metallic corrosion remains a long‐standing challenge in many engineering applications. Specifically, designing a material that can resist corrosion both in abiotic as well as biotic environments remains elusive. Here a lightweight sulfur–selenium (S–Se) alloy is designed with high stiffness and ductility that can serve as an excellent corrosion‐resistant coating with protection efficiency of ≈99.9% for steel in a wide range of diverse environments. S–Se coated mild steel shows a corrosion rate that is 6–7 orders of magnitude lower than bare metal in abiotic (simulated seawater and sodium sulfate solution) and biotic (sulfate‐reducing bacterial medium) environments. The coating is strongly adhesive, mechanically robust, and demonstrates excellent damage/deformation recovery properties, which provide the added advantage of significantly reducing the probability of a defect being generated and sustained in the coating, thus improving its longevity. The high corrosion resistance of the alloy is attributed in diverse environments to its semicrystalline, nonporous, antimicrobial, and viscoelastic nature with superior mechanical performance, enabling it to successfully block a variety of diffusing species. Abstract : S–Se is demonstrated as a universal anticorrosive coating, which is easily processed, mechanically robust, and effective in biotic and abiotic environments. S–Se coatings are effective due to their unique combination of properties, including insulating and impermeable nature, viscoelasticity, and intrinsic antimicrobial properties. The coating also exhibits an ability to recover defects and damage with minimal intervention.